Analysis of legal acts regarding home education in Poland - historical approach - Maria Racewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The purpose of this article is to show legal acts regarding home education in Poland in a historical context. Documents such as the Constitutions, the Educational System Act, the Educational Law Act, Amendments of the Educational System Act and the Ordinance of the Minister of National Education have been reviewed. Based on the above-mentioned documents, legislative changes related to homeschooling introduced over the last few decades have been analysed and presented. The article indicates also the direction of changes in Polish homeschooling and emphasizes difficulties related to them for homeschooling families.